2000
DOI: 10.1177/00220345000790030801
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Computer-assisted Recognition of Different Dental Hard Tissues

Abstract: For pattern recognition, fuzzy set theory has been proven to be highly useful. The aim of the present investigation was to combine the fuzzy set with an ultrasonic scaler, to test its suitability for automatic detection of different tooth substances. An experienced operator placed the tip of a piezoceramic ultrasonic scaler on a tooth, thereby inducing oscillations in the contact area around the ultrasonic tip. Each surface showed a characteristic oscillatory behavior in the immediate vicinity of the tip. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The principle is based on a method described by Strackeljan and Kocher (Strackeljan et al 1997, Kocher et al 2000). The working tip of a conventional, commercially available ultrasonic handpiece bearing a piezoceramic oscillation stimulator is excited by short, low‐power impulses to perform about 50 oscillations/s.…”
Section: Methodsmentioning
confidence: 99%
“…The principle is based on a method described by Strackeljan and Kocher (Strackeljan et al 1997, Kocher et al 2000). The working tip of a conventional, commercially available ultrasonic handpiece bearing a piezoceramic oscillation stimulator is excited by short, low‐power impulses to perform about 50 oscillations/s.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of explorer tips failed to differentiate between burnished residual calculus and cementum and also failed to be an accurate method for subgingival calculus detection (6). Current detection systems are based on measurements of resonance vibrations of ultrasonic treatment or autofluorescence induced by laser irritation (11,12). Furthermore, it has been reported that a complete removal of plaque and calculus was more difficult to achieve in deep pockets than in shallow pockets, whereas the tooth type did not influence the results obtained (8).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of dental surface discrimination dates back to work by Strackeljan (1993), Strackeljan et al (1997) and Kocher et al (2000). The tip of a conventional dental ultrasound scaler receives short, weak impulses, which transform into oscillations of the instruments tip of about 5 μ m at the dental surface.…”
Section: Methodsmentioning
confidence: 99%